Why is Neo-liberalism so Resilient?. (November 2019) - Gamble, Andrew
Neo-liberalism rose to prominence during the stagflation crisis of the 1970s and consolidated its position as the dominant western ideology after the collapse of communism in Europe in the 1990s. Neo-liberalism is not a monolithic doctrine but has several different strands, including Ordoliberalism and Anglo-American economic liberalism. The latter became closely associated with globalisation, financialisation and deregulation, which helped produce the boom in the world economy during the 1990s but also created the conditions for the financial crash in 2008. Despite the scale of that crisis neo-liberalism has remained resilient as an ideology and as a policy regime. Different dimensions of this resilience are explored – the role of the state, geopolitics, class politics, electoral politics, and the hegemony of neo-liberal ideas – and whether this resilience is likely to continue.